Factors Influencing Village Government Resistance To Sub-District Head Policy In The Establishment Of Inter-Village Cooperation Body In Huruna Sub-District, South Nias Regency - Syukur Darman Halawa; Odaligoziduhu Halawa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The objectives to be achieved in this study are to determine the resistance of the Village Government to the Camat policy and to analyze the factors that influence the resistance of the Village Government to the Camat policy in the formation of the Inter-Village Cooperation Agency in Huruna District, South Nias Regency. The type of research used in this study is qualitative research. The sampling technique uses purposive sampling and the main informants in this study are the sub-district head, village secretary, BPD chairman and members, treasurer and the kaur. And additional informants are people who can provide additional information as a complement to the analysis and discussion and qualitative research. The additional informants in this study are several community leaders, village officials and sub-district officials. Data collection techniques use observation, documentation and interviews. From the results of the study, it was obtained that in regional autonomy, there is no cooperation between villages in government affairs and community interests, because each village only takes care of its village and its citizens. Regarding human resources and capacity, there is no cooperation between villages in planning and managing village development. And there is no cooperation between villages in collaborating to create an effort to improve the village economy. The policy implemented by the Sub-district Head has supervised Siforoasi Village and other villages in Huruna District by facilitating the preparation of village regulations, providing guidance, supervision, facilitation, and consultation on the implementation of village administration. As well as evaluating the implementation of village government. The Sub-district Head encourages community participation between villages in sub-district development planning, evaluating community empowerment activities between villages.